PERSPECTIVES ON SKILLS EFFICIENCY OF TRAINERS AND MANAGEMENT OF TRAINING TOWARDS EFFECTIVE TRAINING - Mmabatho Portia APHANE; Moitsadi ZITHA; Jacob Tseko MOFOKENG; Lerato MOFOKENG (International Journal of Social and Educational Innovation)
The purpose of this research was to investigate the characteristics that impact in-service competence trainers to provide effective training in the South African Police Service (SAPS). To find the 500 respondents, this study used a quantitative strategy that relied on a basic random sampling procedure. Respondents, primarily SAPS members from 13 police stations in Gauteng province, South Africa, completed and returned 329 questionnaires in total. The cohort under research was selected using a non-probability sample technique (purposive), which included respondents from  various  ranks who attended various training development sessions at the Johannesburg Training Centre. The findings indicated that the demand for trainers' recruitment is laden with various obstacles, such as the already existing paucity of resources at training centres, lack of communication and transparency, The study also found that more than 70% of respondents said their training is linked with theoretical content and has a direct influence on their daily work. This study provides insights on improving trainer skill efficiency and training management, as well as identifying opportunities for further research. This study offers insight on the elements that influence training quality in the SAPS and proposes appropriate measures for improvement.